2021
DOI: 10.1182/hematology.2021000314
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is an inherited bone marrow failure syndrome, characterized as a rare congenital bone marrow erythroid hypoplasia (OMIM#105650). Erythroid defect in DBA results in erythroblastopenia in bone marrow as a consequence of maturation blockade between the burst forming unit–erythroid and colony forming unit–erythroid developmental stages, leading to moderate to severe usually macrocytic aregenerative (<20 × 109/L of reticulocytes) anemia. Congenital malformations localized mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 45 publications
3
25
0
4
Order By: Relevance
“…Most of the family members in our study presented with steroid-responsive anemia in infancy and subtle congenital malformations, consistent with recent genotype-phenotype studies for RPS19 and RPS vs. RPL-DBA (Arbiv et al, 2018;Iskander et al, 2021). Wide variations in phenotypic expression have been previously observed in families with both small deletions and missense mutations in RPS19 (Willig et al, 1999;Ichimura et al, 2017;Da Costa et al, 2021). Missense mutations in RPS19 have also been reported to be less penetrant than loss of function mutations (Ulirsch et al, 2018), which may help explain the two individuals in our study who were largely unaffected from a hematologic standpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the family members in our study presented with steroid-responsive anemia in infancy and subtle congenital malformations, consistent with recent genotype-phenotype studies for RPS19 and RPS vs. RPL-DBA (Arbiv et al, 2018;Iskander et al, 2021). Wide variations in phenotypic expression have been previously observed in families with both small deletions and missense mutations in RPS19 (Willig et al, 1999;Ichimura et al, 2017;Da Costa et al, 2021). Missense mutations in RPS19 have also been reported to be less penetrant than loss of function mutations (Ulirsch et al, 2018), which may help explain the two individuals in our study who were largely unaffected from a hematologic standpoint.…”
Section: Discussionsupporting
confidence: 90%
“…55 Rpl5 (uL18) and Rps24 (eS24) RPL5 (uL18) is one of the most commonly mutated RP gene found in DBA patients (7%). 1 In 2016, Kazerounian et al 56 reported 2 mouse models with conditional knockout of Rpl5 or Rps24 (eS24). A pGK-gb2 Loxp/FRT-flanked neomycin cassette was inserted into either Rpl5 or Rps24, resulting in deletion of exons 1-8 for Rpl5 and exons 2-3 for Rps24, respectively.…”
Section: Rpl11 (Ul5)mentioning
confidence: 99%
“…Diamond-Blackfan anemia (DBA) is a rare congenital hypoplastic anemia which manifests with moderate or severe macrocytic anemia associated with short stature, physical anomalies involving bone development, and predisposition for malignancies [1][2][3][4][5] . More than 90% of patients are diagnosed during their first year of life (median age 12 weeks).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations